Effect of Cyclone Dana on Standing Rice and Contingency Strategies for Crop Resilience in the Indian Sundarbans Delta - CHATTERJEE, SITESH; DHAR, ANANNYA; DEY, SAIKAT; MANDAL, SUJAN; JANA, SOUJANYA; ROY, KALYAN; GANGOPADHYAY, CHIRASREE (Journal of the Indian Society of Coastal Agricultural Research, 2026)
The coastal zone of West Bengal is more prone to any type of weather aberrations and cyclones, which cause severe harm to the people of coastal habitats. It was just another occasion, when this area encountered a cyclone named ‘Dana’ during 23rd to 25th October, 2024, which caused severe damage to all sectors, including agriculture. Immediately after that, roaming field surveys were conducted on 30th October and 1st November, 2024, to assess the direct impact of this cyclonic storm Dana on standing crops at eight (08) villages across Kakdwip, Namkhana, and Gosaba blocks of South 24 Parganas district of West Bengal. During this time, rice was growing as the predominant crop, and in a few pockets, cultivation of some seasonal vegetables was found. Among the observed effects, waterlogging in low lying areas and stem-lodging of rice (10-70%) were widespread across most fields. However, certain rice varieties exhibited physiological resilience, which enabled them to withstand waterlogged conditions. Additionally, a notable incidence of pests and diseases was recorded with special mention to yellow stem borer, leaf folder, sheath blight, and rot. During the discussions with farmers, agricultural scientists provided suggestions and contingency crop measurements to estimate crop damage and documented the preventive measures already adopted by the farmers.